ATG5 is essential for ATG8-dependent autophagy and mitochondrial homeostasis in Leishmania major. - Roderick A M Williams; Terry K Smith; Benjamin Cull; Jeremy C Mottram; Graham H Coombs (PLoS Pathogens)
Macroautophagy has been shown to be important for the cellular remodelling required for Leishmania differentiation. We now demonstrate that L. major contains a functional ATG12-ATG5 conjugation system, which is required for ATG8-dependent autophagosome formation. Nascent autophagosomes were found commonly associated with the mitochondrion. L. major mutants lacking ATG5 (Δatg5) were viable as promastigotes but were unable to form autophagosomes, had morphological abnormalities including a much reduced flagellum, were less able to differentiate and had greatly reduced virulence to macrophages and mice. Analyses of the lipid metabolome of Δatg5 revealed marked elevation of phosphatidylethanolamines (PE) in comparison to wild type parasites. The Δatg5 mutants also had increased mitochondrial mass but reduced mitochondrial membrane potential and higher levels of reactive oxygen species. These findings indicate that the lack of ATG5 and autophagy leads to perturbation of the phospholipid balance in the mitochondrion, possibly through ablation of membrane use and conjugation of mitochondrial PE to ATG8 for autophagosome biogenesis, resulting in a dysfunctional mitochondrion with impaired oxidative ability and energy generation. The overall result of this is reduced virulence.